Articles Published in Men’s Health Journal in 2022; a Brief Report - Saghaei Dehkordi, Somayeh; Shariatpanahi, Samira (Archives of Men’s Health, 2023)
Men’s Health Journal (MHJ) is a Peer-reviewed journal that started working under the chairmanship and editorship of Dr. Jalil Hosseini, (MD, Professor of Urology) since 2017. MHJ journal is one of the journals at Shahid Beheshti University of Medical Sciences, Tehran, Iran. MHJ’s mission is to study all aspects of Men’s health and illness (Research, Clinical, and Theoretical articles). 18 articles published in 2022, have been authored by more than one hundred researchers from countries, including the United States, India, and Iran such as Shahid Beheshti University of Medical Sciences, Tehran University of Medical Sciences, “Isfahan, Urmia, Ahvaz, Ardabil, Hamedan, Semnan, Shahrood” University. The articles submitted in 2022 have been reviewed by more than a hundred reviewers, and we appreciate the reviewer who cooperated with the journal to improve the quality of the articles.